Gamma and neutron attenuation of Bi2O3/CaO modified borovanadate glasses for radiation shielding applications - Alzahrani, Jamila S.; Alrowaili, Z.A.; Alalawi, Amani; Alshahrani, B.; Al-Buriahi, M.S. (Journal of radiation research and applied sciences, 2024)
This article investigates the attenuation features of gamma and neutron radiations for Bi2O3/CaO modified borovanadate glasses. We assess the attenuation coefficients, half value layer (HVL), and mean free path (MFP) of a glass system under different radiation sources and energies. By using PHITS simulation platform, this investigation involves examining different configurations of the studied glass system, including variations in composition and thickness, to optimize its effectiveness as a shielding material. The simulation findings offer valuable insights into the radiation shielding properties of the glass system involved. The obtained results reveal that there is a significant impact for adding Bi2O3 to enhance the values of attenuation coefficients and then improve the shielding performance of the glassy system involved. For example, LAC values at 15 keV are 59.15, 151.89, and 230.05 cm−1, for VBC-Bi20, VBC-Bi20, and VBC-Bi20, respectively. Moreover, the MAC values of VBC-Bi20 specimen are higher than those different commercial glasses such as RS 253, RS 253 G18, and RS 323 G19. These insights assist in the design and development of efficient radiation shielding materials for practical applications in industries like nuclear and medical fields.